مفهوم الحياة والموت في شعر أبي نواس - Les Saly @ Ghazali Bin Salih (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
This study is about the concept of life and death in Abu Nawwas's poetry, and the reasons that has led the researcher to choose this topic to study are to understand Abu Nawwas's philosophy about life and death through his poetry and poems, to learn about the factors that affected his personality, to understand what drove him to insanity and to learn Abu Nawwas's situation after he repented. To understand Abu Nawwas's philosophy through his poetry, the researcher has selected 40 passages from his poems that represent his philosophy about life and 34 passages that represent his philosophy about death. To achieve the research's goals, the researcher selected two methods. The first is the analytical method to analyse the examples from the poems which speak about life, represent the first phase and other examples about the poet's last few years and the phase of his repentance. The second method is the historical approach, where the researcher follows the phases of the poets and the situations of his era, and the effects upon the philosophy of the poet about life and death. The study has identified the reasons that drove Abu Nawwas to insanity, and his love for worldly life lies in the diversity of civilisations, and the mixture of traditions and cultures, additionally, other reasons include the fact that he was an orphan and his relationship with his waliba.A drinking phase gave him a great chance and a successful way to enjoy his freedom, as he rebelled against his traditions. In that phase, Abu Nawwas revealed his goals and expressed his personality. He then presented the important issues and cases to be discussed in the Abbasi community in his own style and included a personal touch. Abu Nawwas repented and stopped drinking and devoted his days to good deeds and corrected his mentality. His repentance was honest; he did not return to his previous phases in his last days.